A study of prevalence of Mycoplasma pneumoniae pneumonia and validation of Immunoglobulin M for Mycoplasma pneumoniae in the diagnosis of Mycoplasma pneumoniae pneumonia - Kumar, Pragalatha; Patil, Alkarani T; Latha, F J (Indian Journal of Child Health, 2016)
Background: Mycoplasma pneumoniae pneumonia (MPP) is one of the most common causes of childhood community-acquired pneumonia (CAP) and common cause of mortality and morbidity in young children. Polymerase chain reaction (PCR) is promising with higher specificity and superior sensitivity to that of culture or single point serology. Objective: This study was conducted to estimate the prevalence of MPP, and to compare the efficacy of PCR and immunoglobulin M (IgM) enzyme-linked immunosorbent assay (ELISA) for the diagnosis of MPP among CAP in children. Materials and Methods: This study was conducted in children between 2 months and 12 years of age admitted with clinical and radiological features of pneumonia. The children were presumed clinically to have MP infection as per IAP guidelines when they had a cough and fever for more than 5 days. A predesigned proforma was used to collect history and clinical examination findings. Routine investigations such as complete blood count, C-reactive protein, chest X-ray, and blood culture were done. Those suspected of infection with MP infection were further subjected to PCR and IgM ELISA. Results: MP(27%) was found to be an important cause of CAP in children between 2 and 8 years. The most common clinical symptoms were cough and fever (100%) followed by myalgia (20.8%), arthralgia (16.6%), and rashes (12.5%). PCR is the rapid reliable diagnostic test with a sensitivity of 100% and specificity of 93%. IgM ELISA is equally effective diagnostic test with sensitivity of 83% and specificity of 100%. Conclusion: MP is an emerging cause of CAP in school going as well as preschool children. Although PCR is an alternative test of culture, use of simple test like IgM ELISA will reduce the cost of investigation and help us in arriving at definitive diagnosis of MP.